Islamic preaching and its impact on utilization of Shafi’i Mazhab (sect) in Malay archipelago: Specific study on Malaysian experience past and present - Nizaita, Omar; Zulkifly, Muda (Serials Publications, 2017)
The development of propagation of Islam (da’wah) continuing to growing even after death of Muhammad. Many companions of the Prophet Muhammad who left Medina and Hejaz in order to perform the mission of preaching. Malay Archipelago also receive arrival of Islam as early as the first century of Hijrah in the reign of Caliph Muawiyah (99H-101H). This thus leads the spread of Islam affect substantially the application of Shafi’i sect in the area to become dominant sects in Malaysia. This article aims to study the influence of denomination since previous to this day in system administration and Islamic law in the country. The study is important in proving the integrity of the application and receipt by the Shafi’i sect of Malay community as early as from the dissemination of the message of Islam in the Malay Archipelago.